2023
DOI: 10.1021/jacs.2c12952
|View full text |Cite
|
Sign up to set email alerts
|

Operando Spectroscopic Analysis of Axial Oxygen-Coordinated Single-Sn-Atom Sites for Electrochemical CO2 Reduction

Abstract: Sn-based materials have been demonstrated as promising catalysts for the selective electrochemical CO 2 reduction reaction (CO 2 RR). However, the detailed structures of catalytic intermediates and the key surface species remain to be identified. In this work, a series of single-Sn-atom catalysts with well-defined structures is developed as model systems to explore their electrochemical reactivity toward CO 2 RR. The selectivity and activity of CO 2 reduction to formic acid on Snsingle-atom sites are shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…The SAC has the distinctive advantage compared to bulk metal counterparts owing to its unique electronic structure, which not only can be further regulated easily, but also enables it to maximize the efficiency of atom utilization and therefore increase catalytic activity. 11,90–93…”
Section: Sn-based Electrocatalysts For Co2rrmentioning
confidence: 99%
See 3 more Smart Citations
“…The SAC has the distinctive advantage compared to bulk metal counterparts owing to its unique electronic structure, which not only can be further regulated easily, but also enables it to maximize the efficiency of atom utilization and therefore increase catalytic activity. 11,90–93…”
Section: Sn-based Electrocatalysts For Co2rrmentioning
confidence: 99%
“…The SAC has the distinctive advantage compared to bulk metal counterparts owing to its unique electronic structure, which not only can be further regulated easily, but also enables it to maximize the efficiency of atom utilization and therefore increase catalytic activity. 11,[90][91][92][93] The Sn-based single-atom catalysts have also been reported for electrochemical CO 2 RR. Inspired by the fact that Pyridinic-N doped carbons could play a significant role in combining CO 2 and protons, Zhao et al 94 dispersed Sn on N-doped carbon nanofiber (AD-Sn/N-C) atomically and gave insight into the atomic structure of as-prepared catalysts (AD-Sn/N-C1000) by carrying out the aberration-corrected high-angle annual dark field scanning TEM (HAADF-STEM), which suggested that the isolated Sn atoms can be clearly visualized between carbon layers or on the surface of them.…”
Section: Single-atom Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13] For example, Huang and co-workers have designed a series of single-Sn-atom catalysts with well-controlled coordination and electronic structure to explore the detailed structures of catalytic intermediates and the key surface species associated with CO 2 RR. [14] Very recently, Liao et al have studied the influence of small differences in the coordination environments of metal ions in the catalytic active centers on the selectivity of products in the electrocatalytic CO 2 reduction reaction (CO 2 RR). [15] This all reveals the importance of clarifying the structurefunction relationship.Recently, organometallic complexes with nitrogen-coordinated single atoms have been widely reported for electrocatalytic CO 2 RR.…”
mentioning
confidence: 99%